(untitled) (L’uomo nero. Materiali per una storia delle arti della modernità, 2022)
Thanks to continuous connections and passages between literature and art, the essay analyzed the fortune of Gastone Novelli’s work in Claude Simon’s texts, starting from Sebald’s Austerliz novel, where he quoted Claude Simon’s story of Novelli biography in Le Jardin des plants. Interested in visual arts, Simon met the Italian artist in 1961 at Novelli’s personal show at Galérie de Fleuve in Paris: they became friends as well as Simon wrote a presentation for the catalogue of Novelli’s exhibition in New York in 1963.